Antibacterial Activity and Toxicity Profiles of Selected Medicinal Plant Extracts and Conventional Antibiotics against Bacterial Triggers of Some Autoimmune Diseases - Cocis, Amadeus; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Nigella sativa L., Anongessius latifolia (Roxb. ex DC.) Wall. ex Euill. and Perr. and shilajit have been used traditionally to treat numerous infectious diseases, including many caused by bacterial pathogens. However, extracts of these traditionally medicines have been poorly studied and are yet to be tested for the ability to inhibit the growth of bacterial triggers of multiple sclerosis and rheumatic fever. Materials and Methods: Antimicrobial activity of selected plant extracts was assessed using disc diffusion and liquid dilution minimum inhibitory concentration (MIC) assays against some bacterial triggers of multiple sclerosis and rheumatic fever. Interactions between the extracts and conventional antibiotics were studied and classified using the sum of the fractional inhibitory concentration (ΣFIC). The toxicity of the individual samples and the combinations was assessed using the artemia lethality assay (ALA) assay. Results: The methanolic A. latifolia extract displayed notable antibacterial activity against the bacterial triggers of multiple sclerosis (A. baylyi and P. aeruginosa), and rheumatic fever (S. pyogenes). Furthermore, combining the methanolic A. latifolia extract with tetracycline and chloramphenicol resulted in potentiation of the inhibitory activity against P. aeruginosa and S. pyogenes. None of the individual components (nor the combinations) were toxic in the ALA assay. Conclusion: The A. latifolia methanolic displayed clinically relevant antibacterial activity against A. baylyi, P. aeruginosa and S. pyogenes when tested alone. Furthermore, that extract also potentiated the activity of tetracycline and chloramphenicol against some bacteria. The lack of toxicity of the extracts and combinations indicates that these combinations may provide leads in the development of new therapies to prevent and treat the autoimmune diseases multiple sclerosis and rheumatic fever.
Keywords: Medicinal plants; Black caraway; Multiple sclerosis; Rheumatic fever; Conventional antimicrobials; Synergy; Drug interaction; Toxicity.